2007
DOI: 10.2135/cropsci2007.01.0058
|View full text |Cite
|
Sign up to set email alerts
|

Production and Heterosis Analysis of Rice Autotetraploid Hybrids

Abstract: Poor fertility is the main barrier for utilizing heterosis between the two rice (Oryza sativa L.) subspecies, indica and japonica Recently, the development of autotetraploid hybrids (2n = 4x = 48) has been suggested as a new method for increasing heterosis in hybrid rice. Using standard experimental protocols, the elite diploid rice male sterile, maintainer, and restorer lines were colchicine‐doubled, and autotetraploid counterparts were obtained. Seven resulting hybrids were analyzed for heterobeltiosis (HB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
32
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 13 publications
7
32
0
Order By: Relevance
“…Since 1995, we have been focusing on producing autotetraploid rice plants using the cytoplasmic male sterility system including new hybrid combinations with normal seed set for breeder use. To date, many autotetraploid three lines and new hybrid combinations with normal seed set and remarkable heterosis have been selected (Tu et al 2003(Tu et al , 2007. In this study, we used well-distributed SSR markers to analyze the genetic diversity and population genetic structure of 36 autotetraploid three parental lines with normal seed set (Tu et al 2003(Tu et al , 2007) and 14 original diploid three parental lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1995, we have been focusing on producing autotetraploid rice plants using the cytoplasmic male sterility system including new hybrid combinations with normal seed set for breeder use. To date, many autotetraploid three lines and new hybrid combinations with normal seed set and remarkable heterosis have been selected (Tu et al 2003(Tu et al , 2007. In this study, we used well-distributed SSR markers to analyze the genetic diversity and population genetic structure of 36 autotetraploid three parental lines with normal seed set (Tu et al 2003(Tu et al , 2007) and 14 original diploid three parental lines.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many autotetraploid three lines and new hybrid combinations with normal seed set and remarkable heterosis have been selected (Tu et al 2003(Tu et al , 2007. In this study, we used well-distributed SSR markers to analyze the genetic diversity and population genetic structure of 36 autotetraploid three parental lines with normal seed set (Tu et al 2003(Tu et al , 2007) and 14 original diploid three parental lines. The genetic analysis is important to ensure the origin of autotetraploid rice, for maintaining the distinctiveness of autotetraploid varieties, and to differentiate the various genetic backgrounds of autotetraploid rice.…”
Section: Introductionmentioning
confidence: 99%
“…emphasized the limitation of quadrivalent frequencies [10]. Rice fertility in autotetraploids have been fragmentarily studied and there is no report on relationship between cytological behaviors and grain fertility, so far.Some autotetraploid rice hybrids with high seed set were bred [11]. Using these materials, this investigation aimed to reveal the relationship of hybrid fertility with chromosome behaviors during meiosis of autotetraploids.…”
mentioning
confidence: 99%
“…The generation of autooctoploid plant lines through chromosome doubling has been used to create novel germplasms in many breeding programs [19][20][21][22][23][24][25]41]. The development of autopolyploid plants has also been used to overcome the cross incompatibility barrier between different ploidy levels [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The development of autopolyploid plants has also been used to overcome the cross incompatibility barrier between different ploidy levels [42][43][44]. In rice, hybridization of colchicine-induced autotetraploids of indica and japonica varieties displayed enhanced heterosis, which is a beneficial trait for crop improvement (Tu et al, 2007). A recent paper reported that hybrids derived from a cross between the tetraploid upland cv.…”
Section: Discussionmentioning
confidence: 99%